Morphometric studies of Clausena anisata (Willd.) Hook. f. ex. Benth. in coastal savanna zone of Ghana - Essilfie, M.K.; Oteng-Yeboah, A.A. (West African Journal of Applied Ecology, 2013)
Numerical taxonomic study was conducted on five populations of C. anisata in the coastal savanna zone of Ghana to determine their patterns of taxonomic variation and identify diagnostic characters among the populations studied. The results showed that the five populations of C. anisata exhibited complex patterns of morphological variation. The study also revealed that the populations studied could be phenetically classified into two main clusters. The phenetic groupings identified could not be considered as botanical varieties because of the complex patterns of morphological variation. From the numerical character analysis, morphological characters like peduncle length, ratio of sepal length to width, number of floral branches per inflorescence, anther length, style diameter, filament length, style length, plant height, petiole diameter, sepal length and petal length were identified as diagnostic morphological characters. Even though the phenetic groups identified within C. anisata could not be classified as morphological varieties, they could still be described and documented for general purposes such as communication, management and conservation but not for traditional taxonomic purposes.
Keywords: Morphometric studies; Clausena anisata; coastal savanna zone; Ghana